PENGEMBANGAN KOLEKSI “KONTEN INDONESIANA” DI LUAR NEGERI: STUDI KASUS PADA WEBSITE CENTER OF SOUTHEAST ASIA STUDIES UNIVERSITY OF CALIFORNIA, BERKELEY: -> RETRACTED, Artikel ini telah ditarik dari terbitan Jurnal IPI (Ikatan Pustakawan Indonesia) Vol 2 No 1 Tahun 2017 karena penulis terbukti melakukan plagiarisme dengan mengambil tulisan orang lain dan menggunakan namanya sebagai penulis. Bagian depan artikel tetap kami tampilkan untuk menunjukkan keseriusan redaksi dalam menerapkan etika publik - Destiya P. Prabowo (Jurnal IPI (Ikatan Pustakawan Indonesia), 2017)
This paper discusses how the development of collections about Indonesia (Indonesiana) abroad should be done by the National Library as a deposit of knowledge. As a part of human thought and knowledge, the collection of Indonesiana must be managed in order to be utilized by the next generation. This study aims to find out how the prints and recordings of Indonesia produced abroad but not for trading in Indonesia. For example the results of research on Indonesia produced by educational institutions (both by Indonesian citizens and foreigners) abroad. This research uses case study method at Center of Southeast Asia Studies University of California, Berkeley website. The results show that there are many publications which are the results of research on Indonesia published or not by the institutions abroad. This should be a big challenge for the National Library to organize the collection.